Doubting Thomas and Contemporary Education - Miroy, Jovino De Guzman (Archīum Ateneo, 2024)
This paper aims to discuss what kind of training in doubt Filipino students require in the twenty-first century. To answer this question, the study alludes to the figure of Thomas the Doubter. Students often have a great deal of difficulty accepting the need to learn the skills of doubt and inquiry, making them more vulnerable to what Stuart Sim calls “empires of belief.” This essay discusses how reading Sacred Scriptures may lead to improved understanding of the dynamic relationships among inquiry, doubt, and belief. After explaining what doubt and skepticism mean, skepticism in the New Testament will be discussed. It will also interpret the story of Thomas the Doubter showing how doubt is dynamically related to belief. The paper concludes by discussing the kind of training in doubt and skepticism that is crucial today.